Reencantamento do mundo : a Igreja Universal do Reino de Deus e as práticas mercadológicas - Santos, George Brendom Pereira dos (2021)
The Universal Church of the Kingdom of God is one of the largest denominations of the Pentecostal movement in Brazil, not only in terms of number of believers, but also in terms of finances. Thus, the present work presents, within the essence of Weber's text, the sense of disenchantment, applying to the phenomenon that has been running in contemporaneity, which is the inverse proposed by the theorist, which is re-enchantment. Thus, we seek to explain this meaning by presenting a diversity of authors who apply themselves in a very profound way, but without disconnecting from Weber and his fine contact with the meaning of the magified world. Finally, we present the Universal Church as a ready commerce within this world that is magified and secular, without the removal of any gain or loss effect.